Active Mechanical Threading by a Molecular Motor - Bach, Nicolai; Josef, Verena; Maid, Harald; Dube, Henry (Angewandte Chemie International Edition, 2022)
Molecular motors transform external energy input into directional motions and offer exquisite precision for nano-scale manipulations. To make full use of molecular motor capacities, their directional motions need to be transmitted and used for powering downstream molecular events. Here we present a macrocyclic molecular motor structure able to perform repetitive molecular threading of a flexible tetraethylene glycol chain through the macrocycle. This mechanical threading event is actively powered by the motor and leads to a direct translation of the unidirectional motor rotation into unidirectional translation motion (chain versus ring). The mechanism of the active mechanical threading is elucidated and the actual threading step is identified as a combined helix inversion and threading event. The established molecular machine function resembles the crucial step of macroscopic weaving or sewing processes and therefore offers a first entry point to a “molecular knitting” counterpart.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Hemithioindigo; Indigoids; Molecular Machines; Molecular Motors; Photochemistry

Azotriptycenes: Photoswitchable Molecular Brakes - Stockerl, Willibald J.; Reißenweber, Lilli; Gerwien, Aaron; Bach, Nicolai; Thumser, Stefan; Mayer, Peter; Gschwind, Ruth M.; Dube, Henry (Chemistry - A European Journal, 2023)
The control of molecular motions is a central topic of molecular machine research. Molecular brakes are fundamental building blocks towards such goal as they allow deliberately decelerating specific motions after an outside stimulus is applied. Here we present azotriptycenes as structural framework for light-controlled molecular brakes. The intrinsic kinetics and their changes upon azotriptycene isomerization are scrutinized comprehensively by a mixed theoretical and variable temperature NMR approach. With azotriptycenes C−N bond rotation rates can be decelerated or accelerated reversibly by up to five orders of magnitude. Rate change effects are highly localized and are strongest for the C−N bond connecting a triptycene rotor fragment to the central diazo group. The detailed mechanistic insights provide a solid basis for further conscious design and applications in the future.
CRIS-Team Scopus Importer:2023-12-15

Steric Effects on the Thermal Processes of Hemithioindigo Based Molecular Motor Rotation - Huber, Ludwig A.; Thumser, Stefan; Grill, Kerstin; Voßiek, David; Bach, Nicolai; Mayer, Peter; Dube, Henry (Chemistry - A European Journal, 2021)
Tuning the thermal behavior of light driven molecular motors is fundamentally important for their future rational design. In many molecular motors thermal ratcheting steps are comprised of helicity inversions, energetically stabilizing the initial photoproducts. In this work we investigated a series of five hemithioindigo (HTI) based molecular motors to reveal the influence of steric hindrance in close proximity to the rotation axle on this process. Applying a high yielding synthetic procedure, we synthesized constitutional isomeric derivatives to distinguish between substitution effects at the aromatic and aliphatic position on the rotor fragment. The kinetics of thermal helix inversions were elucidated using low temperature 1H NMR spectroscopy and an in situ irradiation technique. In combination with a detailed theoretical description, a comparative analysis of substituent effects on the thermal helix inversions of the rotation cycle is now possible. Such deeper understanding of the rotational cycle of HTI molecular motors is essential for speed regulation and future applications of visible light triggered nanomachines.
CRIS-Team Scopus Importer:2021-06-11
Keywords: ground states; hemithioindigo; molecular motors; photochemistry; rotation mechanisms